The tale of the heike (Stanford Unicersity, Press, 1988)
The Tale of the Heike is known today in numerous versions, probably dating from the thirteenth century to the Edo period (1600 - 1868): some are relatively short, some very long, some have varant titles... and some contain internal evidence suggestive of use by Buddhist preachers.